Synthesis and properties of novel fluorinated poly(arylene ether)s. Issue 9 (13th February 2015) - Tkachenko, Ihor; Purikova, Olha; Bliznyuk, Valery; Shekera, Oleg; Shevchenko, Valery
Abstract Dibromomethylene‐containing monomer with a tetrafluorobenzene central unit was synthesized using 2, 3, 5, 6‐tetrafluoro‐1, 4‐bis(4‐methylphenoxy)benzene as a starting material. This approach enabled preparation of several fluorinated poly(arylene ether)s containing isomeric fragments, with or without allyl or acetyl side groups, which were prepared by interaction of the synthesized tetrafluorobenzene‐based monomer with various types of hydroxyl‐substituted diphenyl ethers. The structure of the synthesized compounds was determined using Fourier transform infrared, 1H NMR and 19 F NMR spectroscopy techniques. Most of the resulting polyethers were soluble in chlorinated, ether‐type or polar amide solvents. The molecular weight, mechanical and thermal properties of the synthesized fluorinated poly(arylene ether)s were studied depending on the inherent isomery of macromolecular chains and the nature of functional groups. Some ways of functionalization of the prepared fluorinated polyethers with epoxy and triethoxysilyl groups were proposed. © 2015 Society of Chemical Industry